New records of coniferous species (Gymnospermae, Pinidae) to the woody non-native flora of Tunisia and North Africa - El Mokni, Ridha (Hacquetia, 2023)
Ten new taxa of gymnosperms are added to the non-indigenous woody flora of Tunisia. Four of them (Cryptomeria japonica, Pinus brutia var. pityusa, Pseudotsuga menziesii var. glauca, Taxodium distichum var. distichum) are also new for the flora of North Africa. Pinus coulteri is here first reported for the Mediterranean Basin. Three genera (Cryptomeria, Pseudotsuga and Taxodium) are firstly recorded for the non-native vascular flora of Africa whereas two genera (Cedrus and Platycladus) are reported for the first time only for the woody flora of Tunisia. Brief descriptions together with filed photographs, global distributions and habitats at national scale are provided. Some taxonomic comments on their distinguishable features as well as updated keys are also presented.